Peran Keluarga, Sekolah, dan Masyarakat dalam Membentuk Identitas Kebudayaan Siswa Sekolah Dasar - Somantri, Diki; Anggraeni Dewi, Dinie; Saeful Hayat, Rizky (Medpro, 2022)
An ideal education is one that involves the role of the family, the role of the school, and the role of the community so that students will have character values based on culture. This study aims to explore the relationship between the roles of family, school, and community in the formation of cultural identity for elementary school students. The research method used is qualitative research with a literature study approach. The subjects of this research are principals, school committees, teachers, students, and communities or parents of students. In education, it is not only the school that is responsible but all components of society. Through cultural understanding, students can develop a sense of pride in their cultural heritage, while strengthening national identity amid the dynamics of globalization. Forming a cultural identity helps students recognize their cultural roots, understand values, and identify themselves within the context of that culture. Cultural identity formation helps strengthen students' character and personality, providing a strong foundation for positive decision-making and ethical behavior. It can be concluded that cultural identity opens up an understanding of the diversity of the world, preparing students to interact with diverse societies in the future.